Effectiveness of the Techniques Applied to Teach Vocabulary in Mbujimayi (International Journal of Scientific Research and Management (IJSRM), 2022)
To solve this problem, I advise teachers to reconsider their choices of the vocabulary teaching techniques and their combination with others paying attention to those likely to achieve lexical competence. I find the use of the dictionary the best technique for teaching vocabulary as the dictionary contains all the elements of vocabulary listed in this paper. Decision makers and teachers should maximise teacher training in dictionary use (in class or out of it) for the good of the learners’ lexical instruction.